Molecular mechanisms underlying hyperoxia-induced lung fibrosis - I-Ting Chen; Liang-Ti Huang; Chih-Cheng Chen; Chung-Ming Chen (Pediatrics and Neonatology, 2022)
Supplemental oxygen is often used to treat newborns with respiratory disorders. Exposure to high concentration of oxygen and long-term oxygen causes inflammation and acute lung injury. The acute inflammatory phase is followed by a fibroproliferative repair phase, leading to lung fibrosis. Many infants with lung fibrosis develop significant respiratory morbidities including reactive airways dysfunction and obstructive lung disease during childhood. Despite the absence of effective treatments and the incomplete understanding regarding mechanisms underlying fibrosis, extensive literature regarding lung fibrosis from in vitro and in vivo hyperoxia-exposed models is available. In this review, we discuss molecular mediators and signaling pathways responsible for increased fibroblast proliferation and collagen production, excessive extracellular matrix accumulation, and eventually, lung fibrosis. We discuss each of these mediators separately to facilitate clear understanding as well as significant interactions occurring among these molecular mediators and signaling pathways.